A study on the appropriate interior design for an institution for the blind in the Philippine setting - Alejandro, Janette C.
The largest population of the physically disabled in the Philippines is composed of the visually impaired. Rehabilitation prepares them to be in the mainstream of the society and that is the main thrust of Ephpheta Rehabilitation Training center for the Blind. This institution is the main emphasis of the study of the researcher. Her objective is to find the appropriate interior design for an institution of the blind particularly the "kitchen". Through comparison and point of reference the researcher aims to improve the living conditions of the blind, for them to enjoy a decent life through proper space planning, accessible features, texture and acoustic application, orientation in design, and the amenities of law. Physical difficulties were met by the researcher in gathering the data since her subjects cannot see. Nevertheless, oral interviews became a new horizon in the exploration of answers for the writer.